2012
DOI: 10.1007/s00415-011-6392-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in the burden of non-motor symptoms in Parkinson’s disease

Abstract: Differences in the expression of non-motor symptoms (NMS) by Parkinson's disease (PD) patients may have important implications for their management and prognosis. Gender is a basic epidemiological variable that could influence such expression. The present study evaluated the prevalence and severity of NMS by gender in an international sample of 951 PD patients, 62.63% males, using the non-motor symptoms scale (NMSS). Assessments for motor impairment and complications, global severity, and health state were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
145
11
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(193 citation statements)
references
References 70 publications
34
145
11
3
Order By: Relevance
“…A recent study on fatigue in early PD found a significant correlation between higher fatigue scores and older age, but when linear regression analysis was applied, only depression and UPDRS activities of daily living subscale remained significant in their population [38]. In contrast with some previous studies, where higher prevalence of fatigue was found in women [39], we found a significant association of MFI domains mental fatigue and reduced motivation with male gender, but only in the secondary fatigue group.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study on fatigue in early PD found a significant correlation between higher fatigue scores and older age, but when linear regression analysis was applied, only depression and UPDRS activities of daily living subscale remained significant in their population [38]. In contrast with some previous studies, where higher prevalence of fatigue was found in women [39], we found a significant association of MFI domains mental fatigue and reduced motivation with male gender, but only in the secondary fatigue group.…”
Section: Discussioncontrasting
confidence: 99%
“…Non-orthostatic type autonomic dysfunction is an umbrella term that includes a wide variety of autonomic symptoms, including urinary and sexual dysfunction, gastrointestinal disturbances, and thermal dysregulation. Our data collection did not parse out these various symptoms; however, prior studies have demonstrated that sexual dysfunction is highly prevalent in men with PD [8] [11], which may underlie the difference in our population. However, other autonomic symptoms have been demonstrated to cluster in women with PD, such as constipation [11].…”
Section: Discussionmentioning
confidence: 98%
“…Our data collection did not parse out these various symptoms; however, prior studies have demonstrated that sexual dysfunction is highly prevalent in men with PD [8] [11], which may underlie the difference in our population. However, other autonomic symptoms have been demonstrated to cluster in women with PD, such as constipation [11]. Further study is warranted in our patient population to better characterize these differences.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the slow progression of the disease in females could be the reason for the predominant tremor that presents more in females than males [27]. Additionally, according to Martinez-Martin et al [37], dyskinesia and depression symptoms in earlier stage than males [44]. Depression has been theoretically linked to the amygdala because the amygdala plays an important role in emotional memory [45].…”
Section: Sex Differences In Parkinson's Disease (Pd)mentioning
confidence: 99%